Evidências científicas da associação entre tratamento ortodôntico e qualidade de vida: revisão sistemática e meta-análise - Rodrigo Andraus de Andrade (2016)
The orthodontic treatment, as an intervention that alters the dental standard, with consequences on the both the oral function and aesthetics, seems to produce significant impacts over the quality of life of the patient. At the very moment the insertion of Orthodontics in the Brazilian public health system (SUS) is promoted, it is vital to establish the consequences of the orthodontic treatment on the quality of life of the individuals, and also of a functional and aesthetic improvement, in order to subsidize proposals of public policies at the reach of the population. The aim of this paper was to carry out a systematic review and meta-analysis of controlled studies about the association between the orthodontic treatment in adolescent and adult patients and the quality of life. The protocol number of this study is PROSPERO CRD42016052043. A systematic research was done through seven databases (PUBMED, Cochrane Library, Web of Science, Controlled-trials Database of clinical trials, Clinical Trials US National Institute of Health, National Institute for Health and Clinical Excellence NICE, and Bireme) and the information was collected independently by two reviewers. The reference lists of relevant papers and review articles were evaluated, as well. The quality of the studies was assessed and the difference between the averages, when obtained, was combined employing random effect models. Forty-one out of 747 publications, potentially eligible, evaluated the impact of the orthodontic treatment in the quality of life in 38 observational studies and 2 randomized clinical trials. Two studies used their own quality of life tools. Among 33 studies, which used validated measurements of quality of life and which could be combined, it was confirmed that the orthodontic treatment results in both positive impacts (when the treatment is over) and negative ones (when the treatment is in course) on the quality of life of the patients. The difference between the standardized mean and the confidence interval of 95% for the groups CPQ 11-14 + OHIP + PIDAQ + OASIS and WHOQOL-BREF + adapted questionnaires was -0,47(-0,80,-0,14) and -0,26(-0,41,-0,10), respectively, employing random effects models. A significant heterogeneity was observed among the studies (I-squared=98%) and the publishing obliquity evidence. The methodological quality varied among the studies. In conclusion, the orthodontic treatment improves the quality of life of adolescents and adults, once the treatment is over. The heterogeneity among the studies is high, and the use of diverse measurements of quality of life hampers the comparison amid the studies. The results of the present paper confirm the relevance of offering orthodontic treatment to the population who need the correction, in light of the gains in terms of quality of life of the individual who undergo treatment, in the long run.